Case report: Transcatheter pulmonary valve-in-valve implantation in a deteriorated self-expandable valve caused by infective endocarditis - Li, Yan-Jie; Pan, Xin; Wang, Cheng; He, Ben (Frontiers in Cardiovascular Medicine, 2022)
Background Infective endocarditis is a complication with high mortality in patients with congenital heart disease, particularly for those with bioprosthetic valve. Case summary We report a case of a 54-year-old female with a history of tetralogy of Fallot who had been surgically repaired using a transannular patch due to severe pulmonary insufficiency with right heart enlargement and presented with worsening dyspnea. She had received transcatheter pulmonary valve implantation (TPVI) 5 years ago. Unfortunately, bioprosthesis-associated infective endocarditis occurred due to dental caries. Given persistent antibiotic medication, she became clinically stable with prosthesis functional recovery. However, dysfunctional bioprosthesis was still detected 3 years later, which was successfully treated by valve-in-valve TPVI with the help of modified buddy wire technique. At a 12-month follow-up after valve-in-valve TPVI, she was completely recovered with improved symptoms of heart failure. Conclusion This is the first report of valve-in-valve TPVI of a self-expandable valve in a degenerated self-expandable valve. The case highlights increased surveillance for infective endocarditis of transcatheter pulmonary valve should be emphasized. Subsequent valve-in-valve TPVI is an effective treatment for valve failure in defined conditions improving the hemodynamics.